Evaluation of trauma patterns in blast injuries using multiple correspondence analysis. (October 2016) - Dussault, Marie Christine; Smith, Martin; Hanson, Ian
Highlights: Multiple correspondence is used to examine patterns of gunshot and blast-related fractures. Cranial fractures are associated with gunshot related deaths. Post-cranial fractures are associated with blast-related deaths. Distinction between cranial and post-cranial trauma can be used in cases of suspected blast trauma in anthropological assemblages. Abstract: Anthropology features little in published literature about blast injuries. Contributions through case studies and experimental research are beginning to expand our understanding of the effect these injuries have on the human skeleton. This study examines blast injury and gunshot related fractures through multiple correspondence analysis (MCA) with the aim of establishing injury patterns between the two types of trauma. Using a sample of 491 individuals from Bosnia, MCA is employed to identify which body regions differentiate between blast or gunshot related fractures. Cranial fractures were more closely associated with gunshot related cases. Post-cranial fractures were associated with blast-related cases. A differentiation in post-cranial and cranial fractures between gunshot and blast related cases was revealed in the samples. The high prevalence of extremity trauma in blast is similar to previous work, but the smaller amount of cranial blast-related fractures differs from previous studies and from what is found in gunshot-related cases. Differentiation of blast and gunshot wound injuries can be made on the human skeleton and can be used to possibly interpret injury mechanism in large skeletal assemblages as well as single cases.